Dynamics analysis and numerical simulations of a delayed stochastic epidemic model subject to a general response function - Li, Fei; Zhang, Shengqiang; Meng, Xinzhu (Computational & applied mathematics, 2019)
This paper proposes a new delayed stochastic epidemic model with double epidemic hypothesis and a general nonlinear response function. The main purpose is to explore the effects of environmental noise and the general nonlinear response function on stochastic dynamics. By constructing appropriate Lyapunov functions and using some novel differential inequality techniques, we first investigate the long-time asymptotic properties of the stochastic delayed system. Moreover, the threshold conditions for the persistence in mean are established. At last, we carry out a series of numerical simulations to illustrate the performance of the theoretical results. The developed theoretical methods and stochastic inequalities techniques can be applied to explore stochastic differential systems with the general response function.